2009
DOI: 10.1177/1533317509340025
|View full text |Cite
|
Sign up to set email alerts
|

The Caregiver’s Burden of Alzheimer Patients: Differences Between Live-In and Non-Live-In

Abstract: The objective of our study was to describe the burden of a sample of 208 live-in/non-live-in caregivers of patients with Alzheimer's disease (AD). We analyzed the statistical correlation between Caregiver Burden Inventory (CBI) and the live-in/non-live-in caregiver status, and between the ''objective burden,'' the cognitive deterioration, functional ability, and psychic and behavioral disorders. Using analysis of variance (ANOVA), the live-in groups of caregivers were compared to each subscale and to the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 53 publications
4
45
0
3
Order By: Relevance
“…5,6,10,16 In our previous descriptive study, we showed that in patients diagnosed with mild to moderate AD, a greater burden was felt by the live-in group compared to the nonlive-in group. 17 The objective of the study was to demonstrate that living with a person with mild to moderate AD increases the burden of live-in caregivers compared to the nonlive-in, even after 6 months. To that end, we correlated the caregivers' burden (live-in/nonlive-in) with their sociodemographic characteristics and in reference to the functional, cognitive, and behavioral aspect of patients with mild to moderate AD.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,10,16 In our previous descriptive study, we showed that in patients diagnosed with mild to moderate AD, a greater burden was felt by the live-in group compared to the nonlive-in group. 17 The objective of the study was to demonstrate that living with a person with mild to moderate AD increases the burden of live-in caregivers compared to the nonlive-in, even after 6 months. To that end, we correlated the caregivers' burden (live-in/nonlive-in) with their sociodemographic characteristics and in reference to the functional, cognitive, and behavioral aspect of patients with mild to moderate AD.…”
Section: Introductionmentioning
confidence: 99%
“…The progressive nature of the disease will naturally mean that the person with dementia will be dependent on a carer for assistance in daily living. The burden of care, particularly during early stages of the disease, is often assumed by the spouse or a close family member [3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…3 Caregivers report that behaviors such as wandering, physical/vocal agitation, and aggression cause some of the greatest strain. 4,5 Transporting the care recipient to healthcare sites can be difficult and is avoided when possible. 6,7 Caregiver burden and strain can result in decreased caregiver health that ultimately contributes to poor outcomes for the individual with dementia (eg, decreased quality of life and early nursing home placement).…”
mentioning
confidence: 99%